Intraspecific Morphological and Genetic Variations within the Populations of Calotropis gigantea (L) W.T. Aiton from Shivalik Hills of Himachal Pradesh, India - Thakur, Shabnam; Verma, Rachna; Kumari, Amita (Asian Journal of Biological and Life Sciences, 2017)
Calotropis gigantea is an important medicinal, drought resistant wild plant of the Himalayas. Present study was aimed to elucidate the intraspecific morphological and genetic variations among the population of C. gigantea in Shivalik hills of Himachal Pradesh, India through morphological and RAPD markers, respectively. The samples of the plant were collected in triplicates (each sample was approximately three km far away from each other) from five districts (Sirmour, Hamirpur, Solan, Una and Kangra) of Himachal Pradesh using purposive sampling method. Different qualitative characters studied were habit, external shape of tree, stem, leaf characters, flower characters (calyx, corolla, and roecium, and gynoecium), fruit and seed. On the basis of above qualitative characters, no variation was observed in all the districts except Hamirpur which could be the results of epigenetic change. Additionally, intraspecific genetic variations of five genotypes were analyzed by RAPD technique using five random operon primers. Five primers have generated a total of 36 bands out of which 28 were polymorphic. Cluster analysis was carried out based on JACCARD's similarity coefficient and the UPGMA clustering method which showed 77% polymorphism among the genotypes. Results revealed a high level of genetic variations between the selected variants.
Keywords: Calotropis gigantea; Intraspecific genetic diversity; Morphological variations; RAPD; UPGMA